THE ROLE OF INTERNAL AUDIT, INTERNAL CONTROL, ORGANIZATIONAL COMMITMENT AND INTEGRITY, IN IMPROVING OPTIMIZATION OF FRAUD PREVENTION AT HOSPITALS IN SIDOARJO - Jena Sarita; Hwihanus Hwihanus; Slamet Riyadi (Fakultas Ekonomi dan Bisnis Universitas Wijaya Putra, 2023)
This research aims to determine the influence of internal control, internal audit, organizational commitment and integrity on fraud prevention at Hospital X in Sidoarjo. In this regard, to maximize rational, measurable and in-depth research results, this research uses quantitative methods. The data source in this research is a primary data source obtained from respondents from distributing questionnaires indirectly or utilizing existing communication media. Meanwhile, the sampling technique in the research used a probability sampling technique (single random sampling), namely a certain number of employees at Hospital X in Sidoarjo. Data obtained using a questionnaire processed using SPSS 23 for 43 employees of Hospital X Sidoarjo. So the results obtained are that internal audit has no significant effect on fraud prevention, internal control has a significant effect on fraud prevention, organizational commitment has a significant effect on fraud prevention, and Integrity has a significant effect on fraud prevention at Hospital X Sidoarjo.